2016
DOI: 10.1097/igc.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Versus Adjuvant Radiation Treatment for Women With Early-Stage Endometrial Carcinoma

Abstract: Our study suggests that women who receive SRT for their locoregional recurrence have worse DSS and OS compared with those matched patients who received ART. Further studies are warranted to develop a high-quality cost-effectiveness analysis as well as accurate predictive models of tumor recurrence. Until then, ART should at least be considered in the management of early-stage EC patients with adverse prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…Among the few studies that have looked at HDR-BT for vaginal recurrent EC, Petignat et al (17), Vargo et al (4), Vance et al (23), Lin et al (2) and Fokdal (39) showed comparable local control, progression-free, and overall survival rates. Petignat et al reported 5-year LC and DFS rates of 100% and 96%, respectively; for patients treated with HDR-BT for isolated vaginal recurrence of FIGO stage I EC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the few studies that have looked at HDR-BT for vaginal recurrent EC, Petignat et al (17), Vargo et al (4), Vance et al (23), Lin et al (2) and Fokdal (39) showed comparable local control, progression-free, and overall survival rates. Petignat et al reported 5-year LC and DFS rates of 100% and 96%, respectively; for patients treated with HDR-BT for isolated vaginal recurrence of FIGO stage I EC.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are comparable to results of our study, despite the predominant utilization of IMRT (90%) and cylinder brachytherapy (73%) in this study. Vance et al (23) reported relatively better 2- and 5-year disease-specific (90%, 77%) and overall survival (84%, 72%) rates among women with early-stage EC (87% FIGO stage I and 13% FIGO stage II disease). Fokdal et al (38) showed 2-year LC of 92%, with disease-free survival and overall survival rates of 59% and 78% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Nag et al and Huh et al revealed 85.8% and 83% 4.5-year DFS in patients administered with EBRT +/− BT [ 29 , 32 ]. In the analysis performed by Vance et al, 77% of patients were disease-free at 4–5 years and were also administered with EBRT +/− BT [ 35 ]. Lower DFS rates were detected at 4.5 years in the studies conducted by Wylie et al, Sears et al, and Kuten et al in 68%, 54%, and 40% of patients, respectively, who were administered with EBRT +/− BT [ 27 , 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding OS, the highest 4.5-year rates were shown by Petignat et al with 96% OS [ 31 ]. Secondarily, Chapman et al, Huh et al, and Vance et al showed 4.5-year OS rates of 77%, 75%, and 72%, respectively, and their cohorts were treated with EBRT +/− BT [ 32 , 35 , 36 ]. Francis et al showed 65% OS at 4.5 years in patients administered with salvage EBRT [ 37 ].…”
Section: Resultsmentioning
confidence: 99%